On the Ground After September 11 : Mental Health Responses and Practical Knowledge Gained. - Danieli, Yael (Taylor and Francis, 2014)
A heartfelt collection of extraordinary first-person accounts that delve into every level of the experience of 9/11Out of the infamy of 9/11 and its aftermath people rose up with courage and determination to meet formidable challenges. On the Ground After September 11: Mental Health Responses and Practical Lessons Gained is a stirring compilation of over a hundred personal and professional first-hand accounts of the entire experience, from the moment the first plane slammed into the North Tower of the World Trade Center, to the months mental health professionals worked to ease the.